2022
DOI: 10.1029/2022jb024575
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic and Tectonic Domains of Central Costa Rica and the Irazú‐Turrialba Volcanic Complex Revealed by Ambient Noise Tomography

Abstract: Subduction driven processes in Costa Rica led to the development of volcanism, forming the active Central Costa Rican Volcanic Front (CCRVF). Located at the southernmost tip of the CCRVF is the active twin volcanic system, the Irazú-Turrialba Volcanic Complex (ITVC), 50 km north-east from Costa Rica's capital city, San Jose (Figure 1). The summits of each volcano are 10 km apart and form a complex that is about 60 km by 45 km at the base. To better understand these magmatic and tectonic domains, establishing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 143 publications
(276 reference statements)
0
1
0
Order By: Relevance
“…Ambient Noise Tomography studies have demonstrated their effectiveness in imaging structures across various scales, including continental 31 , regional 32 , and local scales 33 . This technique has been successfully applied in various volcanic and hydrothermal regions, ranging from hot-spots and rift volcanoes [34][35][36][37][38] , to more complex subduction-related stratovolcanoes [39][40][41][42] , and calderas 43 . The recent development of nodal technologies (e.g., 44,45 ), allows the investigation of highly scattering systems with a great resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Ambient Noise Tomography studies have demonstrated their effectiveness in imaging structures across various scales, including continental 31 , regional 32 , and local scales 33 . This technique has been successfully applied in various volcanic and hydrothermal regions, ranging from hot-spots and rift volcanoes [34][35][36][37][38] , to more complex subduction-related stratovolcanoes [39][40][41][42] , and calderas 43 . The recent development of nodal technologies (e.g., 44,45 ), allows the investigation of highly scattering systems with a great resolution.…”
Section: Introductionmentioning
confidence: 99%